2017
DOI: 10.21037/jtd.2017.11.14
|View full text |Cite
|
Sign up to set email alerts
|

Mitral valve prolapse: an underestimated cause of sudden cardiac death—a current review of the literature

Abstract: Mitral valve prolapse (MVP) is a common valve abnormality in general population. Despite the general belief of a benign disorder, several articles since the 1980s report sudden cardiac death (SCD) in MVP patients, with a substantial percentage of asymptomatic young individuals. The problem is to detect those patients at increased risk and implement methods that are suitable to prevent cardiac arrest. This review investigates the correlation between MVP and SCD, the understanding of the pathophysiology, the str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 32 publications
1
15
2
Order By: Relevance
“…A number of studies commonly reported young age and female sex as likely risk factors. (3)(4)(5)16) A partial similarity was observed between the present study and past studies with regard to age being a risk factor for SCA though it was not revealed as an independent predictor of SCA. It might be because of the exclusion of old patients who experienced SCA or VA due to other concurrent cardiac diseases or other possible causes of SCA rather than MVP.…”
Section: Main Ndingssupporting
confidence: 80%
“…A number of studies commonly reported young age and female sex as likely risk factors. (3)(4)(5)16) A partial similarity was observed between the present study and past studies with regard to age being a risk factor for SCA though it was not revealed as an independent predictor of SCA. It might be because of the exclusion of old patients who experienced SCA or VA due to other concurrent cardiac diseases or other possible causes of SCA rather than MVP.…”
Section: Main Ndingssupporting
confidence: 80%
“…Modifications of the physiological valvular geometry linked to a progressive inappropriate ECM remodeling result in abnormal perception and responsiveness of VIC to mechanical stress which, in turn, may lead to a vicious circle and contribute to perpetuation of the disease [2].These structural defects prevent the complete closure of the valve causing symptoms of prolapse and regurgitation which ultimately lead to heart failure and to a significant morbidity and mortality [6,7]. Besides surgery for the severe forms of MMV, the medical therapies used in some patients aim at limiting the left ventricular remodeling but do not address the primary mechanism of mitral valve dysfunction.…”
Section: Introductionmentioning
confidence: 99%
“…Pre-existing cardiac disease may be associated with systemic adverse reactions and contribute to an impaired response to resuscitation 39. In particular, it is well established that mitral valve disease is a risk factor for arrhythmias and sudden cardiac death 40. Pain or fear of BPG administration could drive a physiological response precipitating decompensation or arrhythmic events.…”
Section: Discussionmentioning
confidence: 99%